Helmintological characterization of giant anteater (Myrmecophaga tridactyla) and lesser anteater (Tamandua tetradactyla) roadkilled on BR-050 and BR-455 highways (Minas Gerais, Brazil) - Oliveira, W. J. [UNESP]; Santos, A. L. Q.; Souza, W. V.; Custodio, A. E. I.; Hoppe, E. G. Lux [UNESP]; Tebaldi, J. H. [UNESP]; Moraes, F. Rosalinski (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Myrmecophaga tridactyla, giant anteater and Tamandua tetradactyla, collared anteater are nationally widespread mammals. Despite that, their populations are in danger, especially the first one, categorized as vulnerable according to the International Union for Conservation of Nature. This study reports the occurrence of helminths in these two anteater species using road killed specimens from BR-050 and BR-455 highways, Triangulo Mineiro region, Minas Gerais state, Brazil. The species were necropsied, and their gastrointestinal organs and contents were opened and examined for parasite recovery. The identification was based on morphological and morphometric features. The species/ genera found for M. tridactyla and T. tetradactyla, their prevalence, as well the organs, were: Gaphidiops dissimilis (33.33% and 0%) in stomach; Gigantorhynchus echinodiscus (25% and 66.66%) in small intestine; Physaloptera magnipapilla (50% and 66.6%) in stomach and Mathevotaenia spp. (25% and 66.66%) in small intestine. Physaloptera magnipapilla was the most common species and a new location was reported for Graphidiops dissimilis. There is a probable overlap in the home range of these animals and a local helminth diversity was described on the study site.
Keywords: anteater; necropsy; helminths